FEEDING A THOUSAND SOULS : WOMEN,RITUAL,AND ECOLOGY IN INDIA AN EXPLORATION OF THE KOLAM - VIJAYA NAGARAJAN (NEW YORK OXFORD UNIVERSITY PRESS, 2019)
Every day millions of Tamil women in southeast India wake up before dawn to create a kolam, an ephemeral ritual design made with rice flour, on the thresholds of homes, businesses and temples. This thousand-year-old ritual welcomes and honors Lakshmi, the goddess of wealth and alertness, and Bhudevi, the goddess of the earth. It is created by hand with great skill, artistry, and mathematical precision.
Keywords: HINDUISM-RITUALS; KOLAM; TAMIL RITES AND CREMONIES